TBNET – Collaborative research on tuberculosis in Europe - Giehl, C. (Akadémiai Kiadó, 2012)
Networking is a key feature of scientific success. The Tuberculosis Network European Trialsgroup (TBNET) was founded in 2006 as a non-profit, non-governmental peer-initiated scientific organization to collaboratively address research priorities in the area of tuberculosis in Europe. Today, TBNET is the largest tuberculosis research organization in Europe with nearly 500 members from 22 EU countries and 49 countries worldwide (www.tb-net.org). Apart from small multicenter basic research studies, a particular strength of TBNET is the performance of large collaborative projects, pan-European multicenter studies and database projects. In recent years, research from TBNET has substantially contributed to the understanding of the management, risk and prognosis of patients with multidrug (MDR) and extensively drug-resistant (XDR) tuberculosis and led to a better understanding of the clinical value of novel tests for the identification of adults and children with tuberculosis and latent infection with Mycobacterium tuberculosis. In 2009, two branches of TBNET were founded to specifically address tuberculosis in the pediatric population (ptbnet) and non-tuberculous mycobacterial diseases (NTM-NET). In addition to the research activities, TBNET is developing expert consensus documents for clinical management and provides training and capacity building especially for members from Eastern European countries, where tuberculosis is still a prevalent health problem.